AQSAM AL-QUR’AN DAN TRADISI SUMPAH MASYARAKAT ARAB JAHILIYAH: ADAPTASI RETORIKA ILAHI - Nihayatul Husna (IAINU Kebumen Prodi IAT, 2025)
This article examines the phenomenon of the Qur'anic Aqsam (Divine Oaths) not merely as a confirmation of Islamic teachings, but as a rhetorical strategy that both adopts and deconstructs the oath tradition of the Arab Jahiliyah community. Using semantic-historical analysis, this paper argues that the Qur'an appropriates the formulation of pagan oaths made by pre-Islamic Arabs. Oaths, which initially centered on tribal honor, ancestors, and time (al-dahr) as fate, became epistemological instruments for proving Tawhid and eschatology. Case studies of Surah Al-'Adiyat and Surah Al-'Asr demonstrate how the form of pre-Islamic oaths was maintained, but their content and orientation underwent a radical shift from tribal anthropocentrism to prophetic theocentrism.